Nonoccupational post-exposure prophylaxis for HIV after sexual intercourse among women in Brazil: Risk profiles and predictors of loss to follow-up. Issue 39 (September 2019) - Grangeiro, Alexandre; Nascimento, Maria Mônica Paulino do; Zucchi, Eliana Miura; Ferraz, Dulce; Escuder, Maria Mercedes; Arruda, Érico; Lotufo, Denize; Munhoz, Rosemeire; Couto, Marcia Thereza
Abstract : Abstract: Access to antiretroviral-based HIV prevention has been marked by sex asymmetries, and its effectiveness has been compromised by low clinical follow-up rates. We investigated risk profiles of women who received nonoccupational post-exposure prophylaxis (nPEP), as well as the rates and predictive factors of loss to follow-up after nPEP initiation. Retrospective study evaluating 501 women who received nPEP between 2014 and 2015 at 5 HIV centers (testing centers-VCT, outpatient clinics, and infectious diseases hospital). Risk profiles were drawn based on the characteristics of the women and their sexual partners, and then stratified by sociodemographic indicators and previous use of HIV prevention services. Loss to follow-up (LTFU) was defined as not presenting for follow-up visits or for HIV testing after nPEP initiation. Predictors of LTFU were analyzed by calculating adjusted prevalence ratios (aPRs). Approximately 90% of women had sexual encounters that met the criteria established in the Brazilian guidelines for nPEP. Those who declared to be sex workers (26.5%) or drug users (19.2%) had the highest social vulnerability indicators. In contrast, women who had intercourse with casual partners of unknown HIV risk (42.7%) had higher education and less experience with previous HIV testing (89.3%) or nPEP use (98.6%). Of the women who received nPEP after sexual intercourse with stable partners, 75.8% had HIV-infected partners. LTFU rate was 72.8% and predictors included being Black (aPR = 1.15, 95% confidence interval [CI]: 1.03–1.30), using drugs/alcohol (aPR = 1.15, 95% CI: 1.01–1.32) and having received nPEP at an HIV outpatient clinic (aPR = 1.35, 95% CI: 1.20–1.51) or at an infectious diseases hospital (aPR = 1.37, 95% CI: 1.11–1.69) compared with a VCT. The risk of LTFU declined as age increased (aPR 41–59 years = 0.80, 95% CI: 0.68–0.96). Most women who used nPEP had higher socioeconomic status and were not part of populations most affected by HIV. In contrast, factors that contribute to loss to follow-up were: having increased social vulnerability; increased vulnerability to HIV infection; and seeking nPEP at HIV treatment services as opposed to at a VCT.